Cloning and functional analysis of a novel DREB transcription factor from Nicotiana benthamiana - GENG Fang; GUO Wei-hua; GUO Yu-shuang; MENG Xian-mei; ZHANG Fang (浙江大学学报. 农业与生命科学版)
A novel dehydration responsive element binding protein(DREB) transcription factor gene named NbDREB2a was isolated from Nicotiana benthamiana using homology-based and RACE technology. The fulllength of the NbDREB2a cDNA was 1 191 bp and was predicted to encode a protein of 330 amino acids with a conserved AP2 domain. Quantitative real-time RT-PCR analysis revealed that NbDREB2a was expressed ubiquitously in tobacco including leaf, root and stem and could be induced by drought, low temperature and high salt stresses. NbDREB2a protein could bind to the DRE element and activate the expression of downstream reporter genes in yeast cells. By using Agrobacterium-mediated transformation, the NbDREB2a gene was successfully introduced into Arabidopsis. Transgenic Arabidopsis with single copy of NbDREB2a was obtained for further research. The results showed that overexpression of NbDREB2a enhanced tolerance to drought and high salt stresses in transgenic Arabidopsis.